(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
In Karakalpak linguistics, a number of tasks were written to study the linguistic differences of folklore, Karakalpak classical poems, as well as the works of later masters of rhetoric. In particular, due to the linguistic differences of folklore works Sh. Abdinazimov, O. Bekbaulov, A. We can note Abdiev’s dissertation. Linguistic features of the works of Berdak Gargabay uly, a great representative of Karakalpak classical literature, were specially studied by Sh. Abdinazimov. Several works of the scientist on the phonetics of the language of Berdak’s works, on the contribution of Berdak to the development of the Karakalpak literary language were published. In 2001 he defended his doctoral dissertation on "The language of Berdak’s works." The language of Azhiniyaz’s works was specially studied by G. Karlybayeva.